160=(x+8)(x+6)

Simple and best practice solution for 160=(x+8)(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 160=(x+8)(x+6) equation:



160=(x+8)(x+6)
We move all terms to the left:
160-((x+8)(x+6))=0
We multiply parentheses ..
-((+x^2+6x+8x+48))+160=0
We calculate terms in parentheses: -((+x^2+6x+8x+48)), so:
(+x^2+6x+8x+48)
We get rid of parentheses
x^2+6x+8x+48
We add all the numbers together, and all the variables
x^2+14x+48
Back to the equation:
-(x^2+14x+48)
We get rid of parentheses
-x^2-14x-48+160=0
We add all the numbers together, and all the variables
-1x^2-14x+112=0
a = -1; b = -14; c = +112;
Δ = b2-4ac
Δ = -142-4·(-1)·112
Δ = 644
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{644}=\sqrt{4*161}=\sqrt{4}*\sqrt{161}=2\sqrt{161}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-14)-2\sqrt{161}}{2*-1}=\frac{14-2\sqrt{161}}{-2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-14)+2\sqrt{161}}{2*-1}=\frac{14+2\sqrt{161}}{-2} $

See similar equations:

| 3.6=w9 | | 2x+60=4x-120 | | 5m-14=18 | | d+6−2=5d+6−2=5. | | Y+4=-6(x+2) | | -3/4x+44=-31 | | Y+2-3x=0 | | x-3/2=-3 | | 10x-8=9x-16 | | f~-12.3=-73.8 | | 2(-10+5x)=90 | | -28-22z+15=31 | | 2x+1/2=2x+1/4 | | a4=5.2 | | Y+4=(6x+12) | | -6=3(g-17)-12 | | 3m-m+4=10 | | 17-15u=-17u-17 | | 2/8w=5/8 | | y=10-3+102 | | 2(q+1)-2=8 | | 35x-7=7(5x+5) | | 2(5x-4)=9x-16 | | (y/5)^2=49 | | 2a-6a-8=12a+8 | | 5x-7(x-2)=26 | | -4/5f+1=-3 | | 7/8-3+1/4x=3/16x×1/4 | | 20g-3g+2g-17g-g=16 | | a/6-2a/4-2/3=a+4/6 | | 4(x-9)+27=79 | | 12-12x+3x^2=7 |

Equations solver categories